Embedded processor system for controllable period-width multichannel pulse width modulation signals - Mazin Rejab Khalil; Laith A. Mohammeed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This paper proposes a sophisticated embedded processor system configured on zynq-xc7z020 field programmable gate array (FPGA) device for generating four channels pulse width modulation signals with variable duty cycles and periods using embedded design techniques. The main advantages of the technique are the high ability to perform a simultaneous control on period and pulse width of the generated signals and a high system design adaptation to choose the number of input/output channels. Controlling the the period and the pulse width is achieved by injecting a digital signal to the designed system to manipulate embedded timers’ operation. Vivado design suite is used to develop the system hard ware in the integrated development environment where the processing unit and peripherals are instantiated and interconnected. A practical aplication program in C language is prepared to make the system act according to the target. The designed system can be used to drive multi-phase D.C to D.C convertors. The system performance is verified by using vivado logic analyzer and chipscope windows. The superiority of the proposed approach over other approaches is that it resulted in a multi-inputs/multi-outputs pulse width modulation system with high controllability on the pulse width and the period that ranges from 15 nsec to 60 sec.